PENGARUH BUDAYA ORGANISASI DAN PENGEMBANGAN SDM TERHADAP DISPLIN KERJA PEGAWAI DENGAN MEDIASI GOOD GOVERNANCE PADA BIDANG LABORATORIUM FORENSIK POLDA JATENG - Heru Budi Sulistyanto; Indarto Indarto; Dyah Nirmala A.J (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
The problem of work discipline in an organization is a special concern for institutions because it affects the whole organization service. This study aims to determine and analyze the influence of Organizational Culture and HR Development on Employee Work Discipline with Good Governance Mediation in the Forensic Laboratory Polda Jateng. This research includes quantitative research. The sample of this study of the Forensic Laboratory that were taken through the census sample method. The analytical method used is multiple regression analysis with SPSS 25 program to test research hypotheses and answer research problems. The results of this study shows that organization and HR development have an effect on good governance, organizational culture and good governance also affect work discipline, but HR development has no effect on work discipline.